The profitability of seasonal mountain dairy farming - Asheim L.J.; Lunnan T.; Sickel H. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The economics of seasonal production of cheese in the mountain is compared with keeping the cows at the farm, investing in a common pasture, or in co-operative dairy farming on rural Norwegian dairy farms. The comparison is based on a linear programming (LP) model supported with Stochastic Dominance with Respect to a Function (SDRF). Mountain dairy farming involves free ranging cows on alpine pastures for about 70 days. The contents of polyunsaturated fatty acids, CLA and various antioxidants in the milk increase when cows graze alpine species rich pastures affecting the health properties, processing properties, chemical content and possibly also the flavour of dairy products. Seasonal mountain cheese production is found to be generally preferable to the other alternatives. The risks are partly related to price but also to yield and output as well as to policy since the profitability depends strongly on subsidies and premiums, and exemption for farm-processed milk in the quota. Investments in farming co-operatives were unprofitable due to less subsidy payments. The effects of calving time, introducing fertilized pastures or night pens, and supplementary feeding to extend the mountain period and sustain milk yields are examined. The premium price for “mountain products“, animal welfare, and farmer co-operation on marketing are discussed.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)